Historical-critical pedagogy and integral human training as a possibility of resistance to BNCC: perspectives for teacher training (Research, Society and Development, 2022)
This article aims to discuss the pedagogical foundations of Integral Human Formation (FHI) in view of the curricular proposal presented by the National Common Curricular Base (BNCC), in order to outline perspectives of resistance in the context of teacher training and in their performance in the construction of the curriculum. local curriculum. The Integral Human Formation has in its theoretical basis the Historical-Critical Pedagogy which proposes a project that forms the autonomous individual, independent and committed to his/her role as a citizen in social life. At FHI, the school is the place for propaedeutic training, for understanding technical, scientific and social-historical processes, as well as for preparing the individual for the world of work. The BNCC, on the other hand, advocates a proposal, based on the Pedagogy of Competencies, reduced to preparing the individual for the job market, transforming the school into an environment of business preparation. In order to develop this debate, an exploratory study of the academic literature on the subject and document analysis was carried out to lay the theoretical foundations of this article. Thus, it was concluded that, in view of the dictates of the BNCC, teacher training in the construction of the curriculum must be guided by resistance to the exclusively technical model, having in the pedagogical foundations of the FHI, recommended by the Federal Institutes (IFs), a path of struggle for the maintenance and improvement of the integrated curriculum as a form of sealing the neoliberal policies that impose a setback scenario for National Education.